Compensatory phenomena in dermatology - Keshavmurthy A Adya; Arun C Inamadar; Aparna Palit (Wolters Kluwer Medknow Publications, 2018)
Compensatory mechanisms in the human body are generally set in action when there is an absence or deficiency of an attribute to make up for the same. Such mechanisms may be intended to compensate for either the quantitative deficiency or functional impairment of an attribute performing a particular function. Frequently, in an attempt to normalize the homeostatic milieu, the compensatory mechanisms may work more than necessary producing undesired effects as well. In this review, we describe some of such compensatory phenomena in relation to clinical, immunological, pathological, and few other aspects of dermatology, as well as such phenomena characterizing some of the dermatotherapeutics.